Nuevas especies de los géneros Cyclanthera Scharad. y Sicyos L. (Sicyeae. Cucurbitaceae) para la flora de México - Lira, Rafael; Rodriguez-Arevalo, Isela (Instituto de Ecología, A.C., 1999)
In this paper Cyclanthera jeffreyi and Sicyos dieterleae are proposed as new. The first one is only known from a single locality in the state of Querétaro, and belongs to the species group of the genus with non-foliolate blades. It seems to be closely related to Cyclanthera dieterleana Kearns & C.E. Jones, from which differs by the presence of herbaceous-membranaceous, ovate-triangular, slightly 3-5-angled-lobate blades, with acuminate-aristate central lobe, corolla creamy-yellowish colored, and conspicuously pedunculate staminate inflorescences. The second species is only known from a few localities in the states of Jalisco and Michoacán. Although similar to Sicyos guatemalensis and S. parviflorus, it can be separated from them by the type and dimensions of the staminate inflorescence, partially free anthers, as well as the dimensions and other fruit features.